Bruxelles : atmosphère 10-32 - Guislain, Albert; Kessels, Willy (Bruxelles : Eglantine, 1932)
Bibliotheek Camille Huysmans
Dedicator: Kessels, Willy, dedicatee: Huysmans, Camille
Frans
Monografie
Keywords: fotografie; Brussel